Report of the Senate Committee on Finance on the condition of the state : January 28, 1865 (Document (Virginia. General Assembly. Senate) ;, 1865)
January 28, 1865 Report of the Senate Committee on Finance regarding the condition of the state, examining the indebtedness, revenues, and probable charges of the state.